Food purchasing and preparation - Briggs, Roy. (Cassell, 2000)
Controlling resources. Health and safety. Food storage, refrigeration and Hygiene. Fish and shellfish. Meat. Poultry and game. Preparations, sauces, dressings and cold soups. Hors-d'oeuvre. Salads. Buffets.